Micro electro discharge machining of non-conductive ceramic using conductive powder mix dielectric fluid - Ali, Mohammad Yeakub; Suieb, Ali Nurhanim; Mohamad Asharaf, Asfana Banu (Medwell Journals, 2016)
This study presents the process development and investigation of the Material Removal Rate (MRR) in micro Electro Discharge Machining (micro-EDM) of non-conductive ceramic zirconia using titanium carbide powder mixed with the kerosene dielectric fluid. Experimental investigation is carried out using 1.0 mm diameter copper electrode with two varying parameters; gap voltage and capacitance. The MRR data are analyzed and an empirical model is developed using design expert software. The optimum parameters for maximum MRR are found to be 86 V gap voltage and 1.0 nF capacitance.